2018
DOI: 10.1089/brain.2017.0549
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Connectivity and Increased Blood Oxygenation Level Dependent Complexity in the Default Mode Network in Individuals with Chronic Fatigue Syndrome

Abstract: The chronic fatigue syndrome / myalgic encephalomyelitis (CFS) is a debilitating disease with unknown pathophysiology and no diagnostic test. This study investigated the default mode network (DMN) in order to understand the pathophysiology of CFS and to identify potential biomarkers. Using functional MRI (fMRI) collected from 72 subjects (45 CFS and 27 controls) with a temporal resolution of 0.798s, we evaluated the default mode network using static functional connectivity (FC), dynamic functional connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…29 In a recent study, Shan et al investigated CFS/ME using the Stroop task and could not find any differences between the groups. 40 However, when they examined the default mode network they found lower functional connectivity between medial prefrontal cortex, left inferior parietal lobule, medial prefrontal cortex and posterior cingulate cortex in CFS/ME. 40 ► Reward and motivation During a reward processing task/gambling task, the CFS/ME group showed significantly reduced activation in the right caudate and right globus pallidus compared with controls.…”
Section: Fmri and Cognition ► Memorymentioning
confidence: 98%
See 1 more Smart Citation
“…29 In a recent study, Shan et al investigated CFS/ME using the Stroop task and could not find any differences between the groups. 40 However, when they examined the default mode network they found lower functional connectivity between medial prefrontal cortex, left inferior parietal lobule, medial prefrontal cortex and posterior cingulate cortex in CFS/ME. 40 ► Reward and motivation During a reward processing task/gambling task, the CFS/ME group showed significantly reduced activation in the right caudate and right globus pallidus compared with controls.…”
Section: Fmri and Cognition ► Memorymentioning
confidence: 98%
“…23 Shan et al 40 found decreased functional connectivity between the medial prefrontal cortex and both inferior parietal lobules. 40 On the other hand, Kim et al 24 reported an increase in functional connectivity between the posterior parietal cortex and the dorsal anterior cingulate cortex, rostral anterior cingulate cortex, middle temporal cortex and precuneus in participants with CFS/ ME compared with healthy controls. 24 Collectively the findings from rs-fMRI studies suggest dysfunctional connectivity across a number of neural networks in CFS/ME.…”
Section: Rs-fmri and Functional Connectivitymentioning
confidence: 99%
“…A SPECT study reported that patients with ME/CFS presented more diffuse and less focal activation patterns than controls when performing the paced auditory serial addition test [19]. We identified 12 task functional MRI studies of ME/CFS [14,16,[20][21][22][23][24][25][26][27][28][29]. Different patterns of blood oxygenation level-dependent (BOLD) signal changes associated with tasks were reported in each article (detailed in SI).…”
Section: Frequent Observations Additional Brain Regions Recruited Formentioning
confidence: 99%
“…Different patterns of blood oxygenation level-dependent (BOLD) signal changes associated with tasks were reported in each article (detailed in SI). Of these 12 studies, 10 articles reported that patients with ME/CFS either recruited additional brain regions or had a greater BOLD response than controls for cognitive tasks but with the same performance [16,[20][21][22][23][24][25][27][28][29], although decreased BOLD activity was also reported in specific regions. Two remaining studies tested basal ganglia function [14] and reward sensitivity [26] and observed lower BOLD changes in basal ganglia in gambling tasks [14] and lower BOLD changes in the putamen in low-reward condition gambling task [26].…”
Section: Frequent Observations Additional Brain Regions Recruited Formentioning
confidence: 99%
“…Just a single study tested TSPO binding through PET imaging study in CFS patients and found an increased widespread brain signal for this marker, an promising indicative of microglial activation [132]. Other imaging studies showed disturbed connectivity in prefrontal cortex and frontal networks in these patients (19,20), as well as impaired glutamate levels in this brain area [133,134]. On the other hand, regarding cytokines, several investigators have measured these markers levels in the blood of CFS patients, and interesting associations between IL-1 and other cytokine levels and fatigue symptoms have been reported [24].…”
Section: Evidence Of Microglial Activation and Pro-inflammatory Cytokmentioning
confidence: 99%